Perspectives for gallotannins neuroprotective potential - current experimental evidences - Kujawski, Radosław; Kujawska, Małgorzata; Ożarowski, Marcin; Baraniak, Justyna; Laskowska, Halina; Nowocień, Tamara; Borowska, Magdalena; Szulc, Michał; Sobczak, Agnieszka; Mikołajczak, Przemysław (Journal of Medical Science, 2016)
Gallotannins are class of hydrolyzable tannins consisting of gallic acid and a sugar moiety. Currently, there is growing interest around a possible neuroprotective effect of this class of phytochemicals, which is suggested to be a result of their active metabolites. Evidence from experimental studies has suggested that tannin-rich plant preparations might be effective at reversing neurodegenerative pathology and age-related declines in neurocognitive performance. This mini-review summarizes, based on experimental studies, current knowledge about diverse neuroprotective abilities of gallotannins, mostly via antioxidant properties and some mechanisms of the effect are proposed including blocking accumulation of nitrites, inhibiting expression and activity of heme oxygenase 1(HO-1), and decreasing degradation of poly(ADP-ribose) glycohydrolase (PARP).
Keywords: neuroprotection; plant extract; gallotannins; galloylated cyanogenic glycosides; poly(ADP-ribose) glycohydrolase; 1,2,3,4,6-penta‑O‑galloyl‑β‑D‑glucopyranose